The Status of Control over the Constitutionality of Laws in Light of the Constitutional Rules Followed in the Arab Maghreb Countries: Algeria, Morocco, )model) - Benlokrichi, Mustapha (Journal of Legal Studies and Researches, 2021)
The purpose of this study is to ensure that the ruling authorities of the Algerian and Moroccan state respect the provisions of constitutional law by defining the constitutional rules in terms of concept and imperative mandate. We are then subject to the guarantees of the entry into force of constitutional rules, focusing on the basic legal guarantee of the control of the constitutionality of laws through the Constitutional Council or the Constitutional Court. To see how effective these guarantees are Theory and Realism.